Penyusunan Laporan Keuangan Berdasarkan SAK Emkm Berbantuan Microsoft Excel Pada UMKM Uncal.Co - Euis Kania; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Micro Small and Medium Enterprises (MSMEs) in Indonesia have a significant role in building the country's economy. But until now there are still many MSMEs that are difficult to grow their business. One of the contributing factors is that there are still many MSMEs who do not realize the importance of compiling financial statements. MSMEs Uncal.Co is one of the convection companies that has not yet made financial statements. The purpose of this research is to find out the financial records that have been done Uncal.Co, design financial statements with Microsoft Excel and compile financial statements based on SAK EMKM. The research method used is a qualitative descriptive method. Data collection techniques are interviews, literature studies, observations and documentation. The result of this study is the design of financial applications using Microsoft Excel 2016 to assist in compiling financial statements based on SAK EMKM in February 2020.